Comparative analysis of two multitask approaches to cognitive training in cardiac surgery patients - I. V. Tarasova; I. N. Kukhareva; T. B. Temnikova; D. S. Kupriyanova; I. D. Syrova; А. S. Sosnina; O. A. Trubnikova; O. L. Barbarash (Российский кардиологический журнал, 2024)
Aim. To compare the incidence of postoperative cognitive dysfunction and neuropsychological changes in the early postoperative period of coronary artery bypass grafting (CABG) in patients who underwent two versions of multitask cognitive training, which involved various cognitive and motor tasks, as well as in a control group.Material and methods. The study included 100 patients after elective CABG. All patients were randomly divided into three following groups: cognitive training (CT) 1 (postural balance combined with mental arithmetic, verbal fluency, and unusual object use tasks) (n=30), CT 2 (simple visual-motor response combined with task on mental arithmetic, verbal fluency and unusual object use) (n=35) and without training (standard postoperative therapy) (n=35). All patients underwent extensive neuropsychological testing before CABG. Reexamination with assessment of postoperative cognitive dysfunction (POCD) was carried out on days 2-3 and upon completion of 5-7 days of training or on days 11-12 after CABG.Results. The presence of POCD on days 2-3 was found in 100% of patients in the study groups. On days 11-12 of CABG, POCD persisted in 17 people (56,7%) from the CT 1 group, in 24 (68,6%) from the CT 2 group, and in 28 (80%) patients in the control group. Significant differences were obtained in the POCD prevalence in the CT 1 and control groups (odds ratio =3,06; 95% confidence interval: 1,02-9,18, p=0,04), but not CT 2 and control groups (odds ratio =1,83; 95% confidence interval: 0,64-5,47, p=0,28).Conclusion. Multitask training using a combination of postural balance and mental arithmetic tasks, verbal fluency, and unusual object use had a greater effect in reducing the POCD incidence in patients after CABG compared with standard postoperative care. The results of this study may be used to develop cognitive rehabilitation programs in cardiology and cardiac surgery.